Prostate Cancer Support Groups: Canada-Based Specialists' Perspectives. (March 2015) - Oliffe, John L.; Chambers, Suzanne; Garrett, Bernie; Bottorff, Joan L.; McKenzie, Michael; Han, Christina S.; Ogrodniczuk, John S.
To understand prostate cancer (PCa) specialists' views about prostate cancer support groups (PCSGs), a volunteer sample of Canada-based PCa specialists ( n = 150), including urologists ( n = 100), radiation oncologists ( n = 40), and medical oncologists ( n = 10) were surveyed. The 56-item questionnaire used in this study included six sets of attitudinal items to measure prostate cancer specialists' beliefs about positive and negative influences of PCSGs, reasons for attending PCSGs, the attributes of effective PCSGs, and the value of face-to-face and web-based PCSGs. In addition, an open-ended question was included to invite additional input from participants. Results showed that PCSGs were positively valued, particularly for information sharing, education and psychosocial support. Inclusivity, privacy, and accessibility were identified as potential barriers, and recommendations were made for better marketing PCSGs to increase engagement. Findings suggest prostate cancer specialists highly valued the role and potential benefits of face-to-face PCSGs. Information provision and an educational role were perceived as key benefits. Some concerns were expressed about the ability of web-based PCSGs to effectively engage and educate men who experience prostate cancer.